Conference of West European Members of Parliament on sanctions against South-Africa. Sule speaking. On the left of him: ter Beek. On the right of Sule: Scholten. Series of 2 photos - Stegeman, Jan,
Conference of West European Members of Parliament on sanctions against South-Africa. Sule speaking. On the left of him: ter Beek. On the right of Sule: Scholten. Series of 2 photos.